Strategy for the Increase of the Catch Landed in the Fishing Port of Sibolga Nusantara, Indonesia - Nainggolan, Linda Laura; Iin Solihin; Tri Wiji Nurani; Darmawan (Engineering And Technology Journal, 2024)
The Sibolga Islands Fishing Port (PPN) has experienced a decrease in the level of operations, as indicated by a decrease in the number of vessel visits, fishing logbook reports, and the amount of fish production landed. Based on the annual report for the period 2019-2023, the number of fishing vessels that submitted logbooks decreased from 5,677 vessels in 2019 to 3,902 vessels in 2022, a significant decrease of 1,775 vessels over the period. This decrease is consistent with the decrease in the number of vessel visits, from 16,795 in 2019 to 13,346 in 2022, or a decrease of 20.54%. The amount of fish landed also decreases significantly, from 29,332 metric tons in 2019 to 20,428 metric tons in 2022 or by 30.35%. This decrease is due to the fact that the catch of the fleet based in Sibolga VAT is not entirely landed in this port, but elsewhere in the catchment area. This condition is an indication that the Sibolga VAT has not fully fulfilled its function as the main port. This research aims to. The research was conducted in Sibolga VAT and around Tangkahan, Sibolga City, North Sumatra Province. The method used is survey method, the type of data collected consists of primary data and secondary data. For primary data, data collection is done through observation, interviews and questionnaires that have been determined based on the research objectives. The results of this study indicate that Sibolga VAT, as a fishing port, has more competent facilities and manpower compared to private ports (tanks). The facilities available in PPN Sibolga, including spacious docks, cold storage, fish auction, and modern loading and unloading equipment, support the efficiency and effectiveness of port operations. In addition, the staff of Sibolga VAT is equipped with better skills and knowledge in managing port operations